1993
DOI: 10.1038/365412a0
|View full text |Cite
|
Sign up to set email alerts
|

Association between proto-oncoprotein Rel and TATA-binding protein mediates transcriptional activation by NF-κB

Abstract: The c-Rel protein is able to associate in vitro and in vivo with the TATA-binding protein (TBP) of the TFIID complex. Coexpression of TBP with c-Rel augments transactivation from the kappa B site in Drosophila Schneider cells. DNA-binding mutants of TBP not only fail to cooperate, but they repress transactivation by c-Rel. There may be a direct communication between kappa B enhancer binding proteins and basal transcription factors which leads to enhanced transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 46 publications
5
91
0
Order By: Relevance
“…It has also been shown that the amino-terminal region of murine c-Rel, corresponding to the domain of RelA that we find to be required for association with Spi, mediates a specific interaction with the TATA-binding protein (TBP) (33). In contrast, the interaction of TBP with chicken c-Rel was mapped to the carboxy-terminal transactivation domain (77).…”
Section: Methodsmentioning
confidence: 58%
“…It has also been shown that the amino-terminal region of murine c-Rel, corresponding to the domain of RelA that we find to be required for association with Spi, mediates a specific interaction with the TATA-binding protein (TBP) (33). In contrast, the interaction of TBP with chicken c-Rel was mapped to the carboxy-terminal transactivation domain (77).…”
Section: Methodsmentioning
confidence: 58%
“…Previous work on the identity of the biological targets for acidic activators in vivo has suggested that these include TBP, TFIIB, and TAF40. Although TBP has been implicated as a target for several transcriptional activators (24,25,44), the fact the TBP also directly contacts a large number of TAFs and basal transcription factors, including RNA polymerase II and TFIIB, has led to some concern as to the in vivo relevance of these in vitro interactions (20,48,50). While TAF40 has been shown to contact the VP16 activation domain (15), this contact is to the C-terminal 452-to-490 sequence and not to the more N-terminal 412-to-456 sequence that, when multimerized, is fully sufficient to activate transcription efficiently (11,41).…”
Section: Discussionmentioning
confidence: 99%
“…These include the highly acidic activation domains in VP16 (50,103), p53 (10,67,72,84,97,108), c-Myc (39), v-Rel and c-Rel (55,118), and E2F-1 (37), as well as other kinds of activation domains found in the adenovirus activator ElA (48,62), the Epstein-Barr virus proteins Zta (64) and R (70), the human T-cell leukemia virus type 1 (HTLV-1) activator Taxl (8), the transactivator Tat of human immunodeficiency virus type 1 (HIV-1) (53), and human c-Fos and c-Jun (85), PU-1 (38), and Spl (20). In certain cases, reduced binding of TBP by activation domains with point mutations that reduce transactivation in vivo has provided evidence for the biological relevance of these interactions (8,50,53,62).…”
mentioning
confidence: 99%